Instrumen Literasi Ekologi untuk Mengukur Kesiapan Berperilaku Ramah Lingkungan Siswa Sekolah Menengah Atas - Isma Aziz Fakhrudin; Puguh Karyanto; Murni Ramli (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to explain the characteristics and determine the validity and reliability of ecological literacy instruments to measure high school student's readiness for environmentally friendly behavior. The method used is development research. The trial sample consisted of eight high schools with adiwiyata status in Karasidenan Surakarta. The sampling technique used proportionate random sampling with a total sample of 440 students. Collecting data using open-ended interview techniques through focus group discussions and questionnaire trials. The results showed that the reliability and validity of the ecological literacy instrument were declared reliable and valid with Cronbach's alpha value of 0.714 in the knowledge aspect and 0.811 in the concern aspect. In conclusion, the ecological literacy instrument developed has the characteristics of an ecological concept that is universal and can be used to measure readiness for environmentally friendly behavior from the aspect of knowledge and concern for the environment. Keywords: Ecological Literacy Instruments, Readiness for Environmentally Friendly Behavior